2006
DOI: 10.1111/j.1472-765x.2006.01939.x
|View full text |Cite
|
Sign up to set email alerts
|

Major secondary metabolites produced by two commercial Trichoderma strains active against different phytopathogens

Abstract: Aims:  Trichoderma harzianum strains T22 and T39 are two micro‐organisms used as active agents in a variety of commercial biopesticides and biofertilizers and widely applied amongst field and greenhouse crops. The production, isolation, biological and chemical characterization of the main secondary metabolites produced by these strains are investigated. Methods and Results:  Of the three major compounds produced by strain T22, one is a new azaphilone that shows marked in vitro inhibition of Rhizoctonia solani,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
194
1
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(212 citation statements)
references
References 19 publications
8
194
1
9
Order By: Relevance
“…Trichoderma spp., also secrete a chemically diverse range of secondary metabolites, including peptaibols, polyketides, pyrones, terpenes, and polypeptides [27,28]. A previous study reported on the significance of secondary metabolites in the antagonistic action of Trichoderma spp., against the pathogenic fungi Pythium ultimum and Rhizoctonia solani [10,29]. We also found that Trichoderma produced a diverse group of metabolites that were species-specific.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Trichoderma spp., also secrete a chemically diverse range of secondary metabolites, including peptaibols, polyketides, pyrones, terpenes, and polypeptides [27,28]. A previous study reported on the significance of secondary metabolites in the antagonistic action of Trichoderma spp., against the pathogenic fungi Pythium ultimum and Rhizoctonia solani [10,29]. We also found that Trichoderma produced a diverse group of metabolites that were species-specific.…”
Section: Discussionmentioning
confidence: 85%
“…Secondary metabolites were extracted from culture filtrates of Trichoderma as previously described [10]. The selected Trichoderma (spore suspension 4.7 9 10 3 CFU/ml) was cultured in one liter of a mineral medium containing (g l -1 of 50 % seawater) peptone (10), glucose (5), MgSO 4 , NH 4 NO 2 (2.4), yeasts extracts (5), ZnSO 4 (0.2), FeSO 4 (0.2) at pH 7.2 and incubated at 28°C with shaking at 180 rpm for 31 days.…”
Section: Extraction and Gas Chromatography-mass Spectrometry (Gc-ms) mentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of emodin-glycosides and physcionglycosides was also pointed from a strain of Dermocytes spp. 98 Strains of Trichoderma aureoviride 99 and T. harzianum 29,100 were found to produce yellow pigment pachybasin (group E 3 ) and also the orange-red pigment chrysophanol (group A 1 ). Both species of Trichoderma polysporum and T. viride 99,101,102 can also produce pachybasin in addition to the emodin and chrysophanol pigments.…”
Section: Kerriamentioning
confidence: 99%
“…They grow on the surface of roots, where then may protect plants against pathogens and enhance growth. Knowledge concerning the behavior of these fungi as antagonists is essential for their effective use, because they can act against pathogen in several ways (Fravel 1988, Howell 1998, Altomare et al 1999, Harman et al 2004, Vinale et al 2006, Degenkolb et al 2006.…”
Section: Introductionmentioning
confidence: 99%